Commissioning and quality assurance procedures for the HDR Valencia skin applicators - Granero, Domingo; Candela-Juan, Cristian; Ballester, Facundo; Ouhib, Zoubir; Vijande, Javier; Richart, Jose; Perez-Calatayud, Jose (Journal of Contemporary Brachytherapy, 2016)
The Valencia applicators (Nucletron, an Elekta company, Elekta AB, Stockholm, Sweden) are cup-shaped tungsten applicators with a flattening filter used to collimate the radiation produced by a high-dose-rate (HDR) 192 Ir source, and provide a homogeneous absorbed dose at a given depth. This beam quality provides a good option for the treatment of skin lesions at shallow depth (3-4 mm). The user must perform commissioning and periodic testing of these applicators to guarantee the proper and safe delivery of the intended absorbed dose, as recommended in the standards in radiation oncology. In this study, based on AAPM and GEC-ESTRO guidelines for brachytherapy units and our experience, a set of tests for the commissioning and periodic testing of the Valencia applicators is proposed. These include general considerations, verification of the manufacturer documentation and physical integrity, evaluation of the source-to-indexer distance and reproducibility, setting the library plan in the treatment planning system, evaluation of flatness and symmetry, absolute output and percentage depth dose verification, independent calculation of the treatment time, and visual inspection of the applicator before each treatment. For each test, the proposed methodology, equipment, frequency, expected results, and tolerance levels (when applicable) are provided.